1992
DOI: 10.1002/cyto.990130114
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric flow cytometric analysis of radiation‐induced micronuclei in mammalian cell cultures

Abstract: A new flow cytometric method is presented that quantifies the frequency of radiation-induced micronuclei in mammalian cell cultures with high precision. After preparing a suspension of main nuclei and micronuclei stained with ethidium bromide and Hoechst 33258, both types of particles are measured simultaneously in a flow cytometer using forward light scatter and three fluorescence emission intensities excited by UV, 488 nm, and by energy transfer from Hoechst 33258 to ethidium bromide. Nonspecific debris over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 23 publications
(25 reference statements)
0
28
0
1
Order By: Relevance
“…Recently, Schreiber et al (14,151 reported on their results with an automated flow cytometer. Their method is based on a separate measurement of the number of BN cells in the cultures and the number of MN in the BN cells.…”
Section: Fenech and Morley (5) Allows Identification Of Cells In Intmentioning
confidence: 99%
“…Recently, Schreiber et al (14,151 reported on their results with an automated flow cytometer. Their method is based on a separate measurement of the number of BN cells in the cultures and the number of MN in the BN cells.…”
Section: Fenech and Morley (5) Allows Identification Of Cells In Intmentioning
confidence: 99%
“…These methods are based on image analysis, laser scanning cytometry, or flow cytometry [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported on the development of a scoring system that may enhance the utility of a flow cytometric procedure originally described by Nüsse and colleagues [7][8][9][10][11]. Most importantly, the new method includes an ethidium monoazide bromide (EMA) staining step in order to label the chromatin of necrotic and mid/late stage apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%